SOCIAL-PHILOSOPHICAL AND PEDAGOGICAL INTERPRETATION OF THE CONCEPTS OF “CREATIVENESS” AND “CREATIVE TASK” (Лучшие интеллектуальные исследования, 2025)
Abstract. This article presents observations on the socio-philosophical and pedagogical interpretation of the concepts of "creativity" and "creative task". The article also analyzes the presentation of the concepts of creativity and creative task in various sources from the author's point of view and presents the author's definitions of these concepts from a personal point of view.Абстрактный. В статье излагаются размышления о социально-философской и педагогической трактовке понятий «творчество» и «творческая задача». В статье также анализируется изложение понятий «творчество» и «творческая задача» в различных источниках с точки зрения автора, а также приводятся авторские определения этих понятий с личной точки зрения.